Zuzana Toth, Tense and Aspect in Italian Interlanguage - Raimo, Anna (Verbum – Analecta Neolatina, 2022)
Zuzana Toth, Tense and Aspect in Italian Interlanguage. Berlin & Boston: Walter de Gruyter. 2020, 278 pp.